A hybrid modification approach of machine-tool setting considering high tooth contact performance in spiral bevel and hypoid gears. (October 2016) - Ding, Han; Tang, Jinyuan; Zhong, Jue; Zhou, Zhenyu
Highlights: Universal machine-tool setting modification considering residual ease-off. Function relationships between high tooth contact performance items and machine-tool settings. Proportional modification design of the optimal machine-tool setting. A novel hybrid machine-tool setting modification considering high tooth contact performances. Abstract: Machine-tool setting modification for spiral bevel and hypoid gears has been continually demanding more strength and less noise in terms of tooth contact performance. However, it only considers ease-off, but ignores tooth contact performance items. In the present paper, a novel hybrid systematic method is proposed to obtain high tooth contact performance by modifying machine-tool settings. In addition to the traditional item, namely residual ease-off, other three items: (i) the maximum contact pressure, (ii) the maximum loaded transmission error, and (iii) the contact ratio are applied to comprehensively evaluate the gear tooth contact performance. The universal machine-tool setting modification only considering the residual ease-off is first applied to identify initial machine-tool settings. Then, the relationships of high tooth contact performance items and machine-tool settings are established based on the loaded tooth contact analysis (LTCA). Finally, after selecting a few machine-tool settings as the optimal variables based on the sensitivity analysis method, a proportional modification is performed by designing different modification schemes about the optimal settings with different proportions and synthetically evaluating their results on multi-objective high tooth contact performance. The numerical instance and test are employed to verify the validity of the proposed hybrid modification.